1994
DOI: 10.1093/oxfordjournals.humrep.a138704
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy: Determinants of reproductive prognosis after ectopic pregnancy

Abstract: The reproductive prognosis of 115 women desiring pregnancy who underwent surgery for ectopic pregnancy between 1985 and 1990 at the Clinica Luigi Mangiagalli, was analysed after a median follow-up period of 26 months (range 2-83). Probability of reproductive events was assessed by a product-limit model. Women who underwent surgery for ectopic pregnancy had a 54% probability of becoming pregnant (cumulative pregnancy rate, CPR), and a 36% probability of giving birth to a child (cumulative livebirth rate, CLB) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Impaired reproductive performance after EP is evident from decreased fertility and high EP recurrence rates 4–6 . Functional status of the remaining Fallopian tube after the first episode of EP is generally accepted as the major determinant of subsequent spontaneous conception 5,7,8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Impaired reproductive performance after EP is evident from decreased fertility and high EP recurrence rates 4–6 . Functional status of the remaining Fallopian tube after the first episode of EP is generally accepted as the major determinant of subsequent spontaneous conception 5,7,8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Scand 76 (1997) Other investigators have found that fertility after treatment for ectopic pregnancy is unrelated to the characteristics of the ectopic pregnancy (size, rupture, location) (1,6,7) or the procedure performed (7)(8)(9), but related to other factors such as a history of infertility, previous abdominal surgery, and the status of the contralateral tube (8,10,11). In contrast, we found a better fertility outcome in patients with smaller size of the ectopic pregnancy, shorter gestational age, lower hCG level at admission, and with shorter time for elimination of hCG.…”
Section: Discussionmentioning
confidence: 99%
“…[15] Therefore, AMH level is accepted as a more reliable and objective indicator of ovarian reserve, compared with traditional measures such as FSH level and antral follicle count (AFC). [16] Some studies have reported decreased fertility outcome following EP treatment (17,18). Job-Job-Spira et al followed up the EP treatment outcomes and reported a post-treatment fertility rate of about 66% among the treated women.…”
Section: Original Articlementioning
confidence: 99%
“…[17] The main reasons that can explain the decreased fertility rate after treatment of EP include age higher than 35 years, tubal abnormality, low socioeconomic state, adnexal adhesion, history of ruptured EP, and type of treatment(medication v/s surgery). [18,19] In a prospective randomized clinical trial, Fernandez et al compared the efficacy of MTX treatment with salpingectomy on subsequent fertility in the women with EP and concluded that MTX is as efficient as laparoscopic salpingectomy surgery in improving subsequent fertility. [20] However, in other study conducted by Fernandez et al, no significant difference in subsequent fertility was reported between MTX and surgical treatments.…”
Section: Original Articlementioning
confidence: 99%